Paratesticular spindle cell rhabdomyosarcoma: A case report of a rare tumor - Han Kun Ng (Pediatric Urology Case Reports, 2020)
Spindle cell rhabdomyosarcoma (RMS) is a rare variant of embryonal rhabdomyosarcoma. This tumor commonly involves paratesticular region of young males. Herein we report a case report of right paratesticular spindle cell rhabdomyosarcoma in a 16-year-old boy, who was referred to us for painless right scrotal mass. Staging computerized tomography (CT) showed no nodal or distant metastasis. The right radical inguinal orchidectomy was performed. Diagnosis of paratesticular spindle cell rhabdomyosarcoma was confirmed by histopathological and immunohistochemical examination. Paratesticular spindle cell RMS is a rare tumor and morphologically it may mimic other spindle cell neoplasms. Immunohistochemistry plays a pivotal role in its diagnosis. Making a correct diagnosis is crucial owing to the different treatment modalities available for this tumor.